History's responsibility, historian's responsibility: the ‘CNV moment’ as a turn point in the historiography of history of the present time and its new challenges (Tempo e Argumento, 2024)
This essay is based on the assumption that, in the Brazilian context, the ‘CNV moment’ has allowed the temporal turn in history to surface more explicitly, which has led historians of the present time to think about epistemological responses to define the field and the ways of working in it. The proposal is based on Hannah Arendt's idea of responsibility for the world, seen herein as a responsibility of history. In its second and largest part, the text goes through the idea of historian's responsibility, based on the triad proposed by Bedárrida (critical, ethical and civic), pointing out and reflecting on some issues of method and theory, such as multidisciplinary work and reflections on temporalities. As for the ethical and civic axes, which I now name social, the central analysis goes through the discussion of truth, unfolding into reflections on factual truth and truth of the method as a way of differentiating oneself from opinion, seeing these and other challenges for a historian who sets out to think through and write about their time.
Keywords: history of the present time; CNV moment; history's responsibility; historian's responsibility